Pengembangan Media Buku Bergambar Untuk Meningkatkan Kemampuan Bahasa Inggris Anak Usia 5-6 Tahun Di TK Az-Zakyyah Desa Kace - kuswari, monika Ii (ICEJ : Islamic Childhood Education Journal, 2024)
This thesis aims 1) to develop learning media in the form of English books to improve English language skills at the age of 5-6 years in understanding the development of picture book media, 2) to determine the feasibility of developing picture book media based on material experts and media experts, and 3 ) to increase the effectiveness of picture book media. With the development of learning media in the form of picture books as motivation or support in learning, it can maximize children's success.This research uses research and development methods with the development steps or processes used by researchers utilizing the ADDIE model which consists of five stages, namely: 1) Analysis or analysis, 2) Design or planning, 3) Development or development, 4) Implementation or use/ implementation, 5) Evaluation or assessment/improvement.The results and discussion of the studies studied in this development reached appropriateness standards from both material experts and media experts who found interest and effectiveness in learning. The conclusions obtained have an appropriateness level for material experts of 66% and media experts of 76%. The results of the t count and t table from the experimental class and control class are 4.83 > 2.20, so Ha is accepted and H0 is rejected, so there is a significant difference in improving children's English language skills.